EFEK ALBENDAZOLE TERHADAP BERAT BADAN DAN GAMBARAN DARAH DOMBA YANG TERINFEKSI DENGAN NEMATODA GASTRO INTESTINAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
ABSTRAK The effects of albendazole on the weight gains of sheep naturally infected with gastrointestinal nematodes was studied. Eight sheep, 8-12 months old, were divided randomly into 2 groups, 4 sheep each. Onegroup was treated with albendazole 4 mg/kg body weight and the other was used as control. Weighting of the animals and blood samples were taken on every 10 days within a period of 50 days post treatment. Blood samples were examined for total RBC, Hb, PCV, and TPP The results showed that the weight gain of the treated group was significantly higher Keywords: albendazole, RBC, Hb, PCV, and TPP